বহুরূপী বাংলা বানাান - Niladri Sekhar Dash (Dakshabharati, 2006)
This book deals with Bengali spellings, differences in Bengali spellings and presents a practical analysis.
Bahurupi Bangla Banan (Multifaceted Bengali Spelling)
Keywords: Bengali; Linguistics; Bengali; Bengali